Phyllosticta cangshanensis sp. nov., an endophytic fungus from Rhododendron decorum in Cangshan Mountain, Yunnan Province, China - Huang, Zi-Yang; Shen, Hong-Wei; Su, Xi-Jun; Luo, Zong-Long (Phytotaxa, 2024)
Species of Phyllosticta (Phyllostictaceae, Botryosphaeriales) are widely distributed across various host plants as pathogens, endophytes, and saprobes. In this study, two endophytic fungal strains were isolated from healthy leaves of Rhododendron decorum and identified based on morphological characteristics and phylogenetic analysis combining five gene loci (ITS, LSU, tef1-α, act, and gpdh). The morphological and phylogenetic evidence support the introduction of a new species, Phyllosticta cangshanensis. A detailed description, illustration, phylogenetic analysis results, and morphological comparisons with similar taxa of the new species are provided.